Gulf Islands, Trinidad, B.W.I. - (:unkn) unknown (My University, 2011)
The postcard show a group of small islands off the north western coast of Trinidad in the Gulf of Paria.
Colour: Black and white; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Islands--Trinidad and Tobago; Dwellings--Trinidad and Tobago; Paria, Gulf of (Venezuela and Trinidad and Tobago)